2014
DOI: 10.1021/ja509531t
|View full text |Cite
|
Sign up to set email alerts
|

Poly(quinoxaline-2,3-diyl)s Bearing (S)-3-Octyloxymethyl Side Chains as an Efficient Amplifier of Alkane Solvent Effect Leading to Switch of Main-Chain Helical Chirality

Abstract: Poly(quinoxaline-2,3-diyl) containing (S)-3-octyloxymethyl side chains was synthesized to investigate the induction of a single-handed helical sense to the main chain in various alkane solvents. The polymer showed an efficient solvent dependent helix inversion between n-octane (M-helix) and cyclooctane (P-helix). After a screening of alkane solvents, it was found that linear alkanes having large molecular aspect ratios induced M-helical structure, and branched or cyclic alkanes having small molecular aspect ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
48
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(54 citation statements)
references
References 29 publications
2
48
1
Order By: Relevance
“…The effect of solvent on the yield and enantioselectivity of the aldol reaction was also observed ( Table 2 , run 5 vs run 7, run 8 vs run 10). Referring to recent studies on the switch of enantioselection by changing reaction solvent [ 59,60 ] and our previous work, [ 49 ] it can be inferred that decreased content of helices in THF affected the catalytic effi ciency, resulting in lower yield and ee value.…”
Section: Asymmetric Aldol Reactionmentioning
confidence: 77%
“…The effect of solvent on the yield and enantioselectivity of the aldol reaction was also observed ( Table 2 , run 5 vs run 7, run 8 vs run 10). Referring to recent studies on the switch of enantioselection by changing reaction solvent [ 59,60 ] and our previous work, [ 49 ] it can be inferred that decreased content of helices in THF affected the catalytic effi ciency, resulting in lower yield and ee value.…”
Section: Asymmetric Aldol Reactionmentioning
confidence: 77%
“…Furthermore, by introduction of (S) 3 octyl chiral side chains, hydrosilylation of styrene afforded opposite enantiomers in high enantioselectivities in n octane (94% ee, R) and in cyclooctane (90% ee, S) (Scheme 28). 29 We have shown that the majority rule effect also play a role in achieving chiral ampli cation. 52,53 First of all, we prepared separately two enantiomeric dl monomers bearing two (S) or (R) 2 butoxymethyl side chains.…”
Section: Asymmetric Catalyses With Pqxphosmentioning
confidence: 88%
“…29 In addition to helix inversion between chloroform and 1,1,2 TCE, it shows inversion between n alkanes and cycloalkanes. Indeed, the 250 mer PQX adopted pure left handed helical structure in n octane, whereas it takes pure right handed helical structure in cyclooctane.…”
Section: Screw Sense Control Through Sergeants and Soldiersmentioning
confidence: 99%
“…[4] Controlling the formation of these entities aids to clarify the role of chiral organization and also opens venues for new applications.T he dynamic switching of the helical sense,o rs tereomutation, is of special relevance to tuning the helicity of adaptable ensembles. Although stereomutation has been amply studied in covalent polymers, [5] it is scarcely reported in supramolecular polymers,d espite their inherent reversibility that could favor switching helicity.S tereomutation in supramolecular assemblies can be achieved using two main approaches:1 )making use of external stimuli such as pH, [6a] guests, [6b] or solvents; [6c,d] and 2) through kinetic traps or pathway complexity. [7] Herein, the chiral features of the supramolecular copolymerization of carbonyl-bridged triarylamines (CBTs) 1-2 is described (Figure 1a and b).…”
mentioning
confidence: 99%